The influence of teacher emotional support on language learners’ basic psychological needs, emotions, and emotional engagement: Treatment-based evidence - Alrabai, Fakieh; Algazzaz, Wala (Studies in Second Language Learning and Teaching, 2024)
This study assessed the influence of a 10-week teacher emotionally supportive quasi-experimental intervention on the perceived teacher emotional support (PTES), basic psychological needs (BPNs) satisfaction, emotions of anxiety and enjoyment, and emotional engagement of learners of English as a foreign language (EFL). Strategies targeting the three dimensions of TES, that is, positive climate, teacher sensitivity, and regard for students’ perspectives, were deployed exclusively in an experimental group (N = 63), which was compared to a control group (N = 58) in which a more typical teaching approach was followed. Classroom observations and questionnaires were used to capture three time points of changes in learner behaviors. The results of multivariate analyses revealed significant positive changes over time in students’ self-reported PTES behaviors, BPNs satisfaction, emotions, emotional engagement and observed behaviors solely in the experimental condition. Learner BPNs satisfaction showed the largest group differences by mid-term treatment. With the continuous deployment of the treatment, the between-group differences peaked toward the end of the experiment for all learner behaviors. The largest variance at this stage was in learner PTES. These experimentally driven findings provide compelling evidence for the advantages of TES pedagogical interventions for second language learners.